Новий клас інтерполяційних інтегральних ланцюгових дробів - Макаров, В.Л.; Демків, І.І. (Видавничий дім "Академперіодика" НАН України, 2008)
An interpolation integral chain fraction for a given nonlinear functional on the continual knot set is constructed. It is a natural generalization of the interpolation chain fraction.